Nagoya Protocol on access to genetic resources and the fair and equitable sharing of benefits arising from their utilization to the convention on biological diversity text and annex (Secretariat on Biological Diversity, United Nations Environmental Programme, 2011)
"This booklet contains the text and annex of the Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Sharing of Benefits Arising from their Utilization to the Convention on Biological Diversity"--Provided by publisher.